2023
DOI: 10.3389/fimmu.2023.1222308
|View full text |Cite
|
Sign up to set email alerts
|

Markers of the ageing macrophage: a systematic review and meta-analysis

Charlotte E. Moss,
Hew Phipps,
Heather L. Wilson
et al.

Abstract: IntroductionAgeing research is establishing macrophages as key immune system regulators that undergo functional decline. Due to heterogeneity between species and tissue populations, a plethora of data exist and the power of scientific conclusions can vary substantially. This meta-analysis by information content (MAIC) and systematic literature review (SLR) aims to determine overall changes in macrophage gene and protein expression, as well as function, with age. MethodsPubMed was utilized to collate peer-revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Like PMNs, macrophages depend on autocrine signaling via P2Y2, A2, and other purinergic receptors to regulate chemotaxis, NLRP3 inflammasome activation, and other cell functions [ 53 – 55 ]. Systemic ATP accumulation could interfere with these purinergic signaling mechanisms and thereby disrupt macrophage functions such as phagocytosis, cytokine secretion, and ROS production that were reported to deteriorate in response to aging [ 56 ]. Further studies are needed to examine the exact mechanisms by which ATP accumulation and aging impact PMNs, macrophages, and other immune cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Like PMNs, macrophages depend on autocrine signaling via P2Y2, A2, and other purinergic receptors to regulate chemotaxis, NLRP3 inflammasome activation, and other cell functions [ 53 – 55 ]. Systemic ATP accumulation could interfere with these purinergic signaling mechanisms and thereby disrupt macrophage functions such as phagocytosis, cytokine secretion, and ROS production that were reported to deteriorate in response to aging [ 56 ]. Further studies are needed to examine the exact mechanisms by which ATP accumulation and aging impact PMNs, macrophages, and other immune cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that monocyte counts between the young and older cohorts were comparable and not likely influencing these changes (10.27 ± 3.13 million vs 9.36 ± 2.9 million, respectively). While research has set out by others to assess changes in macrophage numbers with age, no real consensus has been drawn, with large tissue- and stimulus-specific variation, although it has been suggested that pro-inflammatory populations increase with age (6).…”
Section: Discussionmentioning
confidence: 99%
“…However, how the molecular changes that determine the chronic inflammatory phenotype translate to a decline in function is unclear, a critical gap limiting the development of new immunotherapeutics for ageing. A further barrier to new therapeutics is our current reliance on mouse models, with a lack of studies in humans (6). Here, we sought to measure ageing-related changes in macrophage migration and phagocytosis in a human cohort as a phenotypic marker to identify the molecular changes underlying macrophage ageing.…”
Section: Introductionmentioning
confidence: 99%